2012
DOI: 10.5897/ajb12.1592
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay and enzymatic comparison of six entomopathogenic fungal isolates for virulence or toxicity against green peach aphids Myzus persicae

Abstract: Myzus persicae is an economically important pest infecting more than 40 families of crops throughout the world. Six entomopathogenic fungal isolates, three each of Beauveria bassiana and Verticillium lecanii, were screened for pathogenicity test against the M. persicae to select high virulent isolate with the most suitable application and to determine the role of individual enzyme in its virulence. Two treatments that is, conidial shower (190±23 conidia/mm 2) and filtrate (3 ml filtrate per treatment from six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
6
14
0
Order By: Relevance
“…The results revealed that all tested strains of B. bassiana and L. lecanii could be effective biocontrol agents against aphids. These results are corroborated by the findings of previous studies reporting the efficiency of different strains of B. bassiana and L. lecanii against M. persicae and other aphid species [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed that all tested strains of B. bassiana and L. lecanii could be effective biocontrol agents against aphids. These results are corroborated by the findings of previous studies reporting the efficiency of different strains of B. bassiana and L. lecanii against M. persicae and other aphid species [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…The obtained results were in agreement with those reported by Khan et al (2012). They screened the proteolytic activity of six EPF isolates, three isolates from each of B. bassiana and V. lecanii.…”
Section: Effect Of Limiting Factors On the Proteolytic Activity Of Epsupporting
confidence: 91%
“…The original host of fungus is green peach aphid and geographical origin is Vladivostok, Russia (Khan et al, 2012). The fungus was maintained by culturing on potato dextrose agar (PDA) Petri plates (90 mm diameter) for 30 days at 26°C in dark.…”
Section: Maintenance Of Beauveria Bassiana 70mentioning
confidence: 99%
“…Following the method of Khan et al (2012), 2 mL of 0.02% tween 80 solutions were added to the culture and the spores gently removed from the mycelium using a glass spreader. The spore suspension was collected using a 2 mL syringe and placed in an Eppendorf tube (1.5 mL).…”
Section: Conidial Suspensionmentioning
confidence: 99%